Classroom Practices Through Action Research: A Case Study in Islamic Education - Nurkilat Andiono; Wiwik Hidayati; Munawaratus Syamsiyah; Tutik Umi Athiyah; Rizkiyah Hasanah (Education and Sociedad Journal, 2024)
This research is motivated by the importance of empowering Islamic educators to improve their professional competence through a research-based approach. In facing the changing needs of modern education, educators are faced with the challenge of continuously adapting and innovating. This requires an effective strategy that supports continuous professional development. This study aims to examine the application of action research as a strategy to empower Islamic educators, to encourage the development of competence and innovation in learning practices. The research approach used is qualitative with a case study method. The research subjects involved the head of the madrasah, curriculum and student affairs coordinators, teachers, and students. Data were collected through in-depth interviews, observations of research activities, and document analysis, such as action research reports and school development plans. The data analysis process was carried out through the stages of data condensation, data presentation, and verification to obtain relevant findings. The results of this study indicate that action research is an effective tool for empowering Islamic educators. Action research not only provides space for reflection on learning practices but also encourages innovation and increases collaboration between educators. These findings provide important insights into the implementation of action research in the context of Islamic education and can be the basis for policy development to improve educator professionalism sustainably.